Exploring Alkaloids as Inhibitors of Selected Enzymes - Singh, Ram; Geetanjali; Singh, Vikram (Asian Journal of Chemistry, 2010)
Living organisms possess complex networks of chemical reactions which are controlled by enzymes. Enzymes are responsible for almost all processes in a biological cell to occur at significant rates. Sometimes the functions of these enzymes need to be checked and hence requires isostructural molecules called enzyme inhibitors that can be cellular metabolites, or foreign substances. In this article, literature has been surveyed to provide comprehensive coverage of alkaloids being used as enzyme inhibitors.